Rancang Bangun Aplikasi Presensi Staf Berbasis Qr Code Menggunakan Metode Prototipe( Studi Kasus : PUSKESMAS Desa Gandasoli ) - Arif Rahman Hakim; Bayu Prasetio; Mutiara Andayani Komara (Jurnal Teknologika, 2026)
The advancement of information technology requires health service institutions to enhance administrative effectiveness, particularly in staff attendance management. Currently, the Gandasoli Village Community Health Center relies on a manual attendance system that is inefficient and prone to data errors. This study aims to design and develop a Quick Response Code-based staff attendance application to improve efficiency, accuracy, and transparency in the attendance process. The research employs the prototyping method, encompassing stages of communication, quick planning, quick design modeling, prototype construction, and deployment delivery and feedback. System testing is conducted using black-box testing to ensure application functionality, while usability is evaluated using the System Usability Scale to gather user feedback. The evaluation results yielded an average score of 88, classified within the acceptable category with an excellent rating. These findings demonstrate that the application is user-friendly and feasible for implementation as a staff attendance recording solution at the Gandasoli Village Community Health Center.